2021
DOI: 10.1371/journal.pone.0251363
|View full text |Cite
|
Sign up to set email alerts
|

Auditory evoked potentials: Differences by sex, race, and menstrual cycle and correlations with common psychoacoustical tasks

Abstract: Auditory brainstem responses (ABRs) and auditory middle-latency responses (AMLRs) to a click stimulus were measured in about 100 subjects. Of interest were the sex differences in those auditory evoked potentials (AEPs), the correlations between the various AEP measures, and the correlations between the AEP measures and measures of otoacoustic emissions (OAEs) and behavioral performance also measured on the same subjects. Also of interest was how the menstrual cycle affected the various AEP measures. Most ABR m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
2
3
0
Order By: Relevance
“…Under the assumption that sexrelated difference in ABR latency dispersion has similar effect size to that estimated by Miller (2007), both the current and previous studies would have been underpowered for detecting a dispersion difference and would thus have been likely to show inter-sample discrepancy (Ioannidis 2005; power would have ranged from 22.1% in Schoonhoven et al 2001, who used 12 female, and 12 male participants, to 35.7% in Don et al (1994), who used 23 female, and 20 male participants; in the current study, it would be 35.5%).Whilst the current results revealed no systematic sex difference in derivedband latency dispersion, they showed significant and sizeable sex differences in derived-band wave-V latencies, as well as stacked and derived-band ABR amplitudes. The difference in stacked ABR amplitude is consistent with previously reported sex differences in broadband ABR amplitude (Trune et al 1988;Chan et al 1988;McFadden et al 2021). The difference in derived-band wave-V latencies was constant across derived-band frequencies and was not mirrored in wave I, supporting previous suggestions that sex difference in ABR latencies predominantly reflects difference in neuronal conduction delay resulting from the difference in brain volume (Dempsey et al 1986;Aoyagi et al 1990).…”
Section: Discussionsupporting
confidence: 89%
“…Under the assumption that sexrelated difference in ABR latency dispersion has similar effect size to that estimated by Miller (2007), both the current and previous studies would have been underpowered for detecting a dispersion difference and would thus have been likely to show inter-sample discrepancy (Ioannidis 2005; power would have ranged from 22.1% in Schoonhoven et al 2001, who used 12 female, and 12 male participants, to 35.7% in Don et al (1994), who used 23 female, and 20 male participants; in the current study, it would be 35.5%).Whilst the current results revealed no systematic sex difference in derivedband latency dispersion, they showed significant and sizeable sex differences in derived-band wave-V latencies, as well as stacked and derived-band ABR amplitudes. The difference in stacked ABR amplitude is consistent with previously reported sex differences in broadband ABR amplitude (Trune et al 1988;Chan et al 1988;McFadden et al 2021). The difference in derived-band wave-V latencies was constant across derived-band frequencies and was not mirrored in wave I, supporting previous suggestions that sex difference in ABR latencies predominantly reflects difference in neuronal conduction delay resulting from the difference in brain volume (Dempsey et al 1986;Aoyagi et al 1990).…”
Section: Discussionsupporting
confidence: 89%
“…The authors viewed these GMCs as “unusual” and “anomalous” at the time. In a recent study, McFadden and colleagues reported that these CEOAE and SOAE measures show GMV along with the GMCs reported earlier [ 46 ]. GMCs have also been reported for a range of anatomical measures across brain regions in humans [ 8 , 9 , 21 ] and chimpanzees [ 6 ].…”
Section: Discussionsupporting
confidence: 71%
“…Although sexual selection and sociocultural factors may contribute to GMV for certain traits, a wide variety of traits and morphological measures show GMV with no apparent link to either selection or societal factors (e.g., the GMV in the hearing thresholds reported above, in additional hearing measures [ 46 ], in birthweights, and in blood parameter measures [ 4 ]). The difference in the pattern of X-activation between males and females represented in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Because female hormones are pro-inflammatory [ 14 ] and the inflammation increases the bone turnover [ 9 ], during pregnancy the estrogen increase causes the otosclerosis onset. The same inflammatory trigger could be observed in the presence of hormonal changes during menstrual cycle and aging [ 8 , 9 ]. This (deleterious) estrogen effect has been confirmed by several clinical studies, in which most subjects affected by otosclerosis were women [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 76%
“…Several authors [ 1 , 2 ] have shown that females have better auditory function than men analyzing subjects with sensorineural hearing loss (SNHL) [ 3 ]. These differences can be related to the effects of female hormones (mainly estrogen) [ 4 ] on the inner ear [ 5 , 6 ] and/or on the auditory system [ 7 , 8 ] at birth. In addition, different exposures to sound during life [ 9 ] and/or different comorbidities between females and males [ 9 ] can determine the differences overserved in the auditory thresholds of adults and elderly subjects.…”
Section: Introductionmentioning
confidence: 99%